Information Technology Investment Assessment Using Val IT Framework - Zein, Afrizal; Rozali, Christien (International Journal of Engineering, Science and Information Technology, 2024)
Organizations must evaluate information technology (IT) expenditures to ensure that IT resources' use contributes value and is in line with their strategic goals. This paper investigates how the Val IT Framework can be used as an efficient tool for managing and evaluating IT investments. Val IT offers a thorough framework for assessing IT initiatives' advantages, disadvantages, and risks and their influence on accomplishing company objectives. We examine how the Val IT Framework may enhance accountability, facilitate IT performance monitoring, and increase transparency in investment decision-making through case studies of multiple businesses. The findings demonstrate that the application of Val IT fosters the advancement of improved IT management techniques and raises knowledge of the worth of IT investments. To attain optimal and sustainable outcomes, IT managers and stakeholders are advised by these findings to utilize a framework-based approach when evaluating investments. However, several challenges remain before the framework can be implemented, including a lack of funding, knowledge about it, and opposition to change. Organizations must, therefore, develop a comprehensive plan. To facilitate change adaptation, this plan should offer incremental implementation, adequate training to enable all stakeholders to better understand Val IT and enough resources to support adoption. These steps can assist businesses in more successfully overcoming their existing challenges. By adopting the right approach, businesses may maximize their IT investments and ensure that every dollar invested contributes significantly to achieving their strategic goals. The Val IT Framework serves as both an assessment tool and a roadmap for better, long-lasting results in IT management when used appropriately. This illustrates how crucial it is to make the investment necessary to implement this framework if the business is to be successful and viable in the long run.